The impact of job stress factors on employees job performance at Lembaga Zakat Negeri Kedah - Nur Azra Irdina, Azhar (2018)
Job Stress can affect employees’ job performance. This study was conducted to assess the impact of job stress factors on employees’ job performance at Lembaga Zakat Negeri Kedah (LZNK). This study involved 113 employees at LZNK. Job stress factors and job performance were measured using standard questionnaires adapted from previous studies. The data was collected via self-administrative questionnaire and analysed by using Statistical Package for the Social Science (SPSS) version 22. The Role theory was used to explain the possible relationship between the variables to support research framework. The result of the findings showed that role ambiguity, role conflict, work overload and time pressure have a significant relationship on employees’ job performance. Based on Correlation analysis result showed that role conflict, word overload and time pressure have a positive correlation while there was a negative correlation for role ambiguity on employee’s job performance. Strong relationship occurred between time pressure and job performance while moderate relationship happened between two variables which are role conflict and work overload with job performance. This study showed that employee’s job performance has relationship with role ambiguity, role conflict, work overload and time pressure. Time pressure is the most influence factors of job stress on employee’s job performance. Therefore, for improvement of job performance in workers, different parameters of these four dimensions of job stress should be considered.